The Impact of Assertive Training Techniques on Enhancing Self-Disclosure Among Junior High School Students in Yogyakarta - Putri Luthfiyah Zahra; Muhammad Nur Wangid (STAI Hubbulwathan Duri, 2025)
Self-disclosure is a vital component of effective interpersonal communication, especially among students. This study investigates the impact of assertiveness training on enhancing students' self-disclosure. An experimental design with a non-equivalent control group was utilized. Twelve students were divided into two groups: an experimental group receiving assertiveness training and a control group engaged in discussion techniques. Both groups underwent pretests and posttests. Data were analyzed using the Wilcoxon signed-rank test to determine changes in self-disclosure levels. Pretest results showed no significant difference in self-disclosure between the two groups (sig. = 0.066). Posttest results indicated a significant increase in self-disclosure within the experimental group following assertiveness training (sig. = 0.027). The control group showed no significant changes in self-disclosure after the intervention. The findings suggest that assertiveness training is effective in improving students' self-disclosure, whereas discussion techniques alone do not yield similar outcomes. Assertiveness training significantly enhances students' self-disclosure. This suggests its potential utility in educational settings to foster better interpersonal communication among students.